Diagnostic challenges in patients with suspected Lyme neuroborreliosis - I. M. Poiasnyk (Zaporožskij Medicinskij Žurnal)
Lyme neuroborreliosis is a tick–borne spirochetal infection, which may affect the peripheral or central nervous system at the early or late stages of the disease.